A three-dimensional finite element analysis of the human hip. (3rd October 2018) - Akrami, Mohammad; Craig, Kim; Dibaj, Mahdieh; Javadi, Akbar A.; Benattayallah, Abdelmalek
Abstract: A three-dimensional hip model was created from the MRI scans of one human subject based on constructing the entire pelvis and femur. The ball and socket joint was modelled between the hip's acetabulum and the femoral head to analyse the multiaxial loads applied in the hip joint. The three key ligaments that reinforce the external surface of the hip to help to stabilise the joint were also modelled which are the iliofemoral, the pubofemoral and ischiofemoral ligaments. Each of these ligaments wraps around the joint connection to form a seal over the synovial membrane, a line of attachment around the head of the femur. This model was tested for different loading and boundary conditions to analyse their sensitivities on the cortical and cancellous tissues of the human hip bones. The outcomes of a one-legged stance finite element analysis revealed that the maximum of 0.056 mm displacement occurred. The stress distribution varied across the model which the majority occurring in the cortical femur and dissipating through the cartilage. The maximum stress value occurring in the joint was 110.1 MPa, which appeared at the free end of the proximal femur. This developed finite element model was validated against the literature data to be used as an asset for further research in investigating new methods of total hip arthroplasty, to minimise the recurrence of dislocations and discomfort in the hip joint, as well as increasing the range of movement available to a patient after surgery.